Perceived Comfort and Adaptive Process of Passivhaus 'Participants'. (December 2015) - Zhao, Jing; Carter, Kate
Abstract: Passivhaus methodology leads to buildings with very high thermal efficiency and high levels of airtightness. The focus of research in Passivhaus is energy performance. The experience of occupying a Passivhaus is often overlooked. This research takes into account social factors of comfort among Passivhaus 'participants'; draws comparison between their expectations and evaluations of the 'perceived comfort'; and investigates the behavioural and psychological adaptive processes that contribute to this 'perceived comfort'. A diverse range of Passivhaus projects built in the past few years in the UK is studied with a mixed method approach. The findings suggest a strong correlation between social aspects of comfort and the participants' evaluation of their Passivhaus, where the adaptive processes are potentially reinforced (or reduced) by this association.